Feasibility Study of Meishan Paper-Cutting Inheritance and Innovative Model - Jie, Su; Chaetnalao, Atithep (Journal of Arts and Thai Studies, 2024)
Objectives: Meishan paper-cutting, a significant facet of traditional Chinese paper-cutting art, boasts a rich history and distinctive artistic significance. However, amidst the cultural diversity of modern society, the preservation and evolution of Meishan paper-cutting face novel challenges. This study aims to 1) develop a model for the inheritance and innovation of Meishan paper-cutting, and 2) validate the feasibility of the proposed Meishan paper-cutting inheritance and innovation model. Methods: A participatory research method was used, and seminars within the community were hosted to enlist project participants. Opinions were obtained from experts to assess the feasibility of the proposed model for preserving the heritage and fostering innovation in Meishan paper-cutting. Results: The research yielded six innovative Meishan paper-cutting products with considerable commercial potential. The findings underscore the efficacy of the Meishan paper-cutting innovation model in fostering the preservation and evolution of Meishan paper-cutting. Moreover, it substantiates the high feasibility of the proposed model. Application of this study: This study’s model holds significant reference and inspirational value for the preservation and improvement within other similar traditional art forms.